Work value, emotional intelligence, and work-life balance on career commitment - Fauziah Hasanah; Okki Trinanda (Universitas Negeri Padang, 2021)
The purpose of this study is(1)to determine and identify the effect of work value on career commitment to nurses at Hermina Padang Hospital(2)to determine and identify the effect of emotional intelligence on career commitment to nurses at Hermina Padang Hospital(3)to identify and identify the effect of work-life balance on career commitment of nurses at Hermina Hospital Padang(4)To determine and analyze work values, emotional intelligence, and work-life balance on career commitments in nurses at Hermina Padang Hospital. The population in this study were all nursing employees at Hermina Hospital, Padang City, with 80 employees. The sampling technique was taken using total sampling where the number of samples was the same as the population, namely 80 people. This data collection uses a questionnaire with a Likert scale and the analytical technique using SPSS 25.